Do plankton reflect the environmental quality status? The case of a post-industrial Mediterranean Bay. (September 2020) - Margiotta, Francesca; Balestra, Cecilia; Buondonno, Angela; Casotti, Raffaella; D'Ambra, Isabella; Di Capua, Iole; Gallia, Roberto; Mazzocchi, Maria Grazia; Merquiol, Louise; Pepi, Milva; Percopo, Isabella; Saggiomo, Maria; et al.
Abstract: While the effects of industrial contamination in coastal areas may persist for years in benthos communities, plankton should not show permanent impairments because of their high spatial dynamics, fast turnover times and pronounced seasonality. To test this hypothesis, in 2019 we conducted five surveys in the Bay of Pozzuoli (Gulf of Naples, Mediterranean Sea), in front of a dismissed steel factory and in the adjacent inshore coastal waters. High seasonal variability was observed for bacteria, phytoplankton and mesozooplankton, whereas plankton spatial gradients were relatively smooth during each survey. Plankton biomass and diversity did not reveal any effects of past industrial activities not even at the innermost stations of the Bay, which however showed some signals of present anthropogenic pressure. Hydrodynamic and morphological features likely play a prominent role in maintaining a relatively good status of the plankton of the Bay, which hints at the relevance of coastal circulation and meteorological dynamics to revitalize areas impacted by human activities. Highlights: Plankton from a former industrial area do not appear to be impacted by pollution. Diversified communities with few non-indigenous species and no anomalies in carbon partition. No harmful algal blooms, no excessive total bacterial concentrations and low incidence of pathogenic bacteria. Active exchange with offshore waters keeps under control present and past anthropogenic impacts.